A class of reconfigurable parallel mechanisms with five-bar metamorphic linkage. (June 2017) - Tian, Chunxu; Fang, Yuefa; Guo, Sheng; Qu, Haibo
This paper presents a planar five-bar metamorphic linkage which has five phases resulting from locking of motors. Reconfigurable limbs are constructed by integrating the five-bar metamorphic linage as sub-chains. The branch transition of metamorphic linkage is analyzed. By adding appropriate joints to the planer five-bar metamorphic linkage, reconfigurable limbs whose constraint can switch among no constraint, a constrained force and a constrained couple are obtained. Serial limb structures that can provide a constraint force and a constraint couple are synthesized based on screw theory. Reconfigurable limbs that have five configurations associated with the five phases of the five-bar metamorphic linkage are assembled with 4-DOF (degrees-of-freedom) serial chains. A class of reconfigurable parallel mechanisms is derived by connecting the moving platform to the base with three identical kinematic limbs. These parallel mechanisms can perform various output motion modes such as 3T, 3R, 2T1R, 1T2R, 3T1R, 2T2R, 1T3R, 2T3R, 3T2R and 3T3R. Finally, the potential application of the proposed mechanisms is analyzed and conclusions are drawn.